2016
DOI: 10.1093/nar/gkw048
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the combined effect of RNA-binding proteins and microRNAs in post-transcriptional regulation

Abstract: Recent studies show that RNA-binding proteins (RBPs) and microRNAs (miRNAs) function in coordination with each other to control post-transcriptional regulation (PTR). Despite this, the majority of research to date has focused on the regulatory effect of individual RBPs or miRNAs. Here, we mapped both RBP and miRNA binding sites on human 3′UTRs and utilized this collection to better understand PTR. We show that the transcripts that lack competition for HuR binding are destabilized more after HuR depletion. We a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 46 publications
2
34
0
Order By: Relevance
“…As a result, these regions have been excluded from previous works analyzing the combined effect of RBPs and miRNAs in post-transcriptional regulation [26]. In our analysis, we observed that the number of RBPs that target a hotspot weakly correlates with mRNA expression (S14 Fig) regardless of the use of mFDR and RNA-seq normalization of CLIP data.…”
Section: Discussionmentioning
confidence: 81%
“…As a result, these regions have been excluded from previous works analyzing the combined effect of RBPs and miRNAs in post-transcriptional regulation [26]. In our analysis, we observed that the number of RBPs that target a hotspot weakly correlates with mRNA expression (S14 Fig) regardless of the use of mFDR and RNA-seq normalization of CLIP data.…”
Section: Discussionmentioning
confidence: 81%
“…For example, integrative analysis of RBP binding and miRNA binding data will allow identification of cooperative and competitive combinatorial patterning of these regulatory factors (90,91). POSTAR represents an early step toward achieving these goals.…”
Section: Discussionmentioning
confidence: 99%
“…1B; Lin and Bundschuh 2015). An analogous mechanism has been proposed for cooperativity between proteins and miRNAs (Kedde et al 2010;Xue et al 2013;Hafezqorani et al 2016). RNA structural cooperativity (RSC) is particularly intriguing as a biological regulatory mechanism as it allows cooperativity and site occupancy to be adjusted individually for each RNA target via sequence.…”
Section: Introductionmentioning
confidence: 99%